2022
DOI: 10.3390/s22020495
|View full text |Cite
|
Sign up to set email alerts
|

Robust Assembly Assistance Using Informed Tree Search with Markov Chains

Abstract: Manual work accounts for one of the largest workgroups in the European manufacturing sector, and improving the training capacity, quality, and speed brings significant competitive benefits to companies. In this context, this paper presents an informed tree search on top of a Markov chain that suggests possible next assembly steps as a key component of an innovative assembly training station for manual operations. The goal of the next step suggestions is to provide support to inexperienced workers or to assist … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 41 publications
0
4
0
Order By: Relevance
“…In [7], it was demonstrated that, through gradient boosted decision trees (GBDT), the best coverage of the assembly sequences could be obtained. In [72], an informed tree search supported by a Markov chain (A* algorithm with first order Markov model) was studied. The proposed method outperformed the decision trees (DT).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In [7], it was demonstrated that, through gradient boosted decision trees (GBDT), the best coverage of the assembly sequences could be obtained. In [72], an informed tree search supported by a Markov chain (A* algorithm with first order Markov model) was studied. The proposed method outperformed the decision trees (DT).…”
Section: Resultsmentioning
confidence: 99%
“…Compared to the operator's reaction speed, the system is orders of magnitude faste (real time), minimizing the wait time for the operator between the time the current assem bly task is finished and the time the next assembly task instruction is provided. More in formation about the concept of the prototype or other implementation details can be found in [70][71][72].…”
mentioning
confidence: 99%
“…Based on data gathered between 2010 and 2020, Gellert et al (2022) created projections for the industrial sector using the Markov approach. They asserted that hydropower represented Romania's most recent and cutting-edge renewable energy source.…”
Section: Introductionmentioning
confidence: 99%
“…Yaghoubi et al [ 11 ] introduced quantitative tools using the Markov method and improved the quality of the oil product line. The Markov model applications also include battery production systems [ 12 ], machine tool modeling [ 13 ], k-out-of-n systems [ 14 , 15 ], reconfigurable production systems [ 16 ], maintenance policy [ 17 ], re-entrant production systems [ 18 ], primary care [ 19 ], rolling bearing monitoring [ 20 ], industrial network models [ 21 ], assembly assistance systems [ 22 ], laser-based manufacturing process [ 23 ], and the steel production process [ 24 , 25 ].…”
Section: Introductionmentioning
confidence: 99%